First‐in‐human study of deucravacitinib: A selective, potent, allosteric small‐molecule inhibitor of tyrosine kinase 2. Issue 1 (22nd November 2022) - Catlett, Ian M.; Aras, Urvi; Hansen, Lars; Liu, Yali; Bei, Di; Girgis, Ihab G.; Murthy, Bindu
Abstract: This randomized, double‐blind, single‐ and multiple‐ascending dose study assessed the pharmacokinetics (PKs), pharmacodynamics, and safety of deucravacitinib (Sotyktu™), a selective and potent small‐molecule inhibitor of tyrosine kinase 2, in 100 (75 active, 25 placebo) healthy volunteers (NCT02534636). Deucravacitinib was rapidly absorbed, with a half‐life of 8–15 h, and 1.4–1.9‐fold accumulation after multiple dosing. Deucravacitinib inhibited interleukin (IL)‐12/IL‐18‐induced interferon (IFN)γ production ex vivo in a dose‐ and concentration‐dependent manner. Following in vivo challenge with IFNα‐2a, deucravacitinib demonstrated dose‐dependent inhibition of lymphocyte count decreases and expression of 53 IFN‐regulated genes. There were no serious adverse events (AEs); the overall frequency of AEs was similar in the deucravacitinib (64%) and placebo (68%) groups. In this first‐in‐human study, deucravacitinib inhibited IL‐12/IL‐23 and type I IFN pathways in healthy volunteers, with favorable PK and safety profiles. Deucravacitinib is a promising therapeutic option for immune‐mediated diseases, including Crohn's disease, psoriasis, psoriatic arthritis, and systemic lupus erythematosus.